Awareness regarding preconception care among bachelor level students, Banepa - Manandhar, Maiya Shobha; Subedi, Durga (Journal of Chitwan Medical College, 2018)
Background: Preconception care means care and counseling that is provided to future parents. The objective of the study was to identify the level of awareness regarding preconception care among bachelor level students. Methods: A descriptive cross sectional study was carried out with bachelor level students from 4 different colleges of Banepa. Samples were selected using cluster sampling. Data was collected through self-administered questionnaire. The data was analyzed using descriptive and inferential statistics. Results: In the study, 59.9% of the respondents had fair awareness and 20.2% had low awareness and only 18.9% had high awareness regarding preconception care. There is significant association between information acquired and level of awareness (p=0.026) and source of information and level awareness (p= 0.069). Conclusion: In overall, respondents had fair awareness with higher level in prevention of teratogenic exposure. There is significant association between information acquired and source of information and level of awareness.